A Comparative Study on Closed Reduction vs. Open Reduction Techniques in the Surgical Treatment of Rotated Lateral Condyle Fractures of the Distal Humerus in Children - Liuqi Weng; Liuqi Weng; Yujiang Cao; Yujiang Cao; Ge Zhang; Ge Zhang; Hai Zhou; Hai Zhou; Xing Liu; Xing Liu; Yuan Zhang; Yuan Zhang (Frontiers in Pediatrics, 2022)
ObjectiveThe best approach between closed reduction and open reduction in the treatment of total displaced and rotated LCFs is still being debated. This study aimed to comparatively evaluate the clinical outcomes and complications of closed reduction vs. open reduction in the treatment of displaced and rotated lateral condyle fractures in children.MethodsWe retrospectively evaluated 46 children who underwent surgical treatment for totally displaced and rotated lateral condyle fractures. Thirty-one children underwent open reduction and percutaneous pinning (ORPP). Ten children underwent closed reduction and percutaneous pinning (CRPP). Five children were changed to ORPP procedures because of the failure of closed reduction attempts. Clinical outcomes and complications in the groups were compared.ResultsAmong three groups, no significant differences were found in demographic variables, and no differences were detected in the incidence of postoperative complications and clinical parameters. The ORPP group had the shortest surgical duration of the three groups (p < 0.005). Patients in CRPP group had faster fracture healing than the patients who underwent open reduction procedures. However, the success of CRPP seemed to be dependent on the earlier surgical intervention.ConclusionORPP is still the first-line treatment for the totally displaced and rotated lateral condyle fractures because of its direct visualization of the joint surface and easy-to-accomplish characteristics. In addition, CRPP may be a feasible option for the treatment of this type of fractures because of it is less invasive and potentially minimizes complications. However, the technical difficulties of CRPP must be taken into account.